Neuromodulation of Hippocampal-Prefrontal Cortical Synaptic Plasticity and Functional Connectivity: Implications for Neuropsychiatric Disorders - Ruggiero, Rafael Naime; Rossignoli, Matheus Teixeira; Marques, Danilo Benette; de Sousa, Bruno Monteiro; Romcy-Pereira, Rodrigo Neves; Lopes-Aguiar, Cleiton; Leite, João Pereira (Frontiers in Cellular Neuroscience, 2021)
The hippocampus-prefrontal cortex (HPC-PFC) pathway plays a fundamental role in executive and emotional functions. Neurophysiological studies have begun to unveil the dynamics of HPC-PFC interaction both in the immediate demands and in long-term adaptations. Disruptions in HPC-PFC functional connectivity can contribute to psychiatric symptoms observed in mental illnesses, such as schizophrenia, depression, and anxiety disorders. Given this role in cognition and disease, it is crucial to understand the mechanisms that modulate the communication in HPC-PFC circuits. Two of the main mechanisms that regulate HPC-PFC communication are synaptic plasticity and modulatory neurotransmission. Synaptic plasticity can be investigated using long-term potentiation or long-term depression protocols, while functional connectivity can be inferred by local field potential synchrony measures. In turn, several neurotransmitters, such as dopamine, serotonin, noradrenaline, and endocannabinoids, can fine-tune regulate HPC-PFC connectivity. Despite experimental evidence, it is unclear what are the effects of synaptic plasticity neurotransmitter modulation on HPC-PFC communication from cellular to behavioral levels. The literature currently lacks a systematic review that focused on the main neurotransmitter interactions in HPC-PFC activity. Here we review the role of these neuromodulatory systems on synaptic plasticity and connectivity dynamics of the HPC-PFC pathway. We reviewed studies showing the effects of the main neurotransmitter system in HPC-PFC synaptic plasticity, both on long- and short-term forms of synaptic plasticity. We also looked for the neuromodulatory effects on the synchrony of brain oscillations during behavior. Finally, we review new approaches from optogenetic and chemogenetic manipulations that have enabled new causal evidence linking HPC-PFC activity, neuromodulation, and maladaptive behaviors. The comprehensive overview of these impairments could help better understand the role of neuromodulation and synaptic plasticity on HPC-PFC circuits and generate insights about the etiology and physiopathology of psychiatric conditions.